Effects of nonlinear pedagogy on performance and movement beahviour of sprint running in amateur sprinters - Neo, Aik Jin Clement (2017)
Nonlinear (NL) pedagogy, driven by key concepts in constraint-led approach, attempts to enhance motor learning of novel skills. It has proven its worth in skill acquisition through manipulation of information which promotes the interaction of key constraints to develop movement pattern solution desirable and efficient for the learner. It has also seen success in enhancement of team performance in game play setting. This study aims to develop nonlinear pedagogy further by investigating its effects on sprint running which is fundamentally a continuous skill. 12 participants were recruited and assigned to either control or nonlinear group whereby the latter will receive additional interventions which encompasses various key principles of nonlinear pedagogy. Time taken for 40 metres sprint during test sessions will be used as performance indicator. Kinematics (movement pattern, stride length, cadence, and ground contact time) and kinetics (maximum applied force) data of the participants through the training sessions will be investigated for changes in movement behaviour. Trunk position changes through the training sessions were significantly different between the two groups (p=.025 < .05). Increase in maximum applied force of right steps and increase in stride length were significant in NL group (p=.002 < .05) and control group (p=.022 <.05) respectively. Though most observations were not statistically significant, NL-guided training design with appropriate coaches’ intervention showed potential in manipulating movement behaviour in a continuous skill. In addition, coaches have to acknowledge individual differences between learners and deploy appropriate constraint to facilitate the process in achieving desired movement outcome.